Environmental Conflicts, Migration and Governance - Kreiger, Tim; Panke, Diana; Pregernig, Michael (Bristol University Press, 2020)
EPDF available Open Access under CC-BY-NC-ND licence. The globalized era is characterized by a high degree of interconnectedness across borders and continents and this includes human migration. This has led to new governance challenges and, at times, populist political backlashes. A key driver of migration is environmental conflict and this is only likely to increase with the effects of climate change. Providing invaluable insights into urgent questions surrounding migration, climate change and conflict, this book is essential for researchers across social science.